Design and optimization of vibration energy harvester for naval ship applications - Lee, Chun Yu (2014)
The paper reviews on linear piezoelectric harvesters (PEH) with the research focus on the substrate material strength and optimal geometric parameters. The application of the PEH is targeted at powering wireless sensors in naval ships, eliminating the use of traditional battery sources that are costly in maintenance and detrimental to the environment in its disposal. The wireless sensors nodes are capable to monitor the ambient temperature, pressure, gas toxicity, fire detection and strain, which are useful in naval ship applications. For comparison between power produced and required, the average power consumption of LORD Microstrain DVRT-Link-Displacement sensor node is 15 mW while a PEH with the substrate geometrical parameters of 90 mm in length, 10mm width and 0.6 mm in thickness operating at 14 Hz and 0.2 g acceleration is able to produce an approximate output power of 2 mW.